2011
DOI: 10.1097/prs.0b013e3181fad34d
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant Complication Review: Double Capsules and Late Seromas

Abstract: Double capsules and late seromas are a relatively new problem in breast augmentation surgery. The problem was not seen in smooth saline or smooth silicone gel breast implants but only in aggressively textured implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
1
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(119 citation statements)
references
References 13 publications
3
97
1
18
Order By: Relevance
“…The second hypothesis propose a mechanical etiology: the detachment of the implant from the capsule would be determined by shear stresses applied to the implant-capsule complex, leading to the creation of a new inner layer of capsule over the implant, from seeding of cells coming from the seroma-like fluid accumulating between the implant and the original capsule (16).…”
Section: Double Capsulesmentioning
confidence: 99%
“…The second hypothesis propose a mechanical etiology: the detachment of the implant from the capsule would be determined by shear stresses applied to the implant-capsule complex, leading to the creation of a new inner layer of capsule over the implant, from seeding of cells coming from the seroma-like fluid accumulating between the implant and the original capsule (16).…”
Section: Double Capsulesmentioning
confidence: 99%
“…Endoscope assistance may be helpful in these cases. Capsulotomy may also be performed when needed [17][18][19][20]. The request or need for size change was the cause of revision in 15.4% of the cases.…”
Section: Discussionmentioning
confidence: 96%
“…Breast enlargement is due to seroma formation. This condition is seen primarily with aggressively textured Biocell implants (11,12). HallFindlay (11) has suggested that the initial adherence of the capsule to the textured implant could become separated.…”
Section: Discussionmentioning
confidence: 99%